Template assisted hydrothermal synthesis of bismuth vanadate for Rhodamine B photodegradation - Essenni, Said; Ali Khan, Moonis; El kaim billah, Rachid; Jeon, Byong-Hun; Sundaramurthy, Suresh; Agunaou, Mahfoud (Journal of molecular liquids, 2024)
[Display omitted] •Hydrothermal method for BiVO4 synthesis using ecologically and economically appealing directing agents.•Characterization results revealed significant impact of chitosan (Cs) on BiVO4 synthesis.•BiVO4-Cs exhibited the highest specific surface area (SSA: 12.27 m2/g) among synthesized oxides.•At neutral pH, BiVO4-Cs showed remarkable RhB photodegradation efficiency under UV-B and visible light. Developmental and technological activities result in uncontrollable release of synthetic dyes into water reservoirs posing potential threat to flora and fauna. Thus, the development of suitable process to treat these waste effluents is urgently needed. Herein, a facile technique was employed to synthesize bismuth vanadate (BiVO4) by incorporating Chitosan (Cs) and Triblock pluronic 123 (P) as directing agents through the hydrothermal process and its efficacy as a photocatalyst was tested for Rhodamine B (RhB) photodegradation. It is noteworthy that the use of Cs as template during the synthesis of BiVO4 had not been previously documented. The synthesized materials were subject to a comprehensive array of characterization techniques, including XRD, FTIR, UV–visible diffuse reflection, SEM, TEM, N2 adsorption isotherm, and XPS analyses. The outcomes revealed that the synthesized catalysts have a monoclinic scheelite structure and displayed an irregular morphology. In addition, the particle size decreased remarkably with the use of Cs. The XPS revealed that the templates have a major influence on the surface charge of the material, as revealed by point of zero charge (pHPZC) analysis. Notably, BiVO4-Cs exhibited the highest specific surface area (SSA: 12.27 m2/g) among them. The synthesized photocatalysts exhibited high catalytic stability. Additionally, the photocatalysts showed excellent RhB photodegradation performance of 94.2 and 64.4 % under UV-B and visible light illumination, respectively.